Barbados. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Barbados during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as agribusiness, trade, agrotourism, family gardens, production, competitiveness, food security, pest and non-communicable diseases control. Finally, technical cooperation was provided in the management and storage of water, sanitation and safety, and in the value chains of fruits and vegetables.